Analysis of Byd’s Market-Seeking Fdi Strategy in the Thai Electric Vehicle Industry: An Eclectic Paradigm Perspective - Kalila Calya Maheswari; Resa Rasyidah (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study analyzes BYD's market-seeking Foreign Direct Investment (FDI) orientation in the Thai electric vehicle industry using the Eclectic Paradigm (Ownership, Location, Internalization/OLI) framework. The study's contribution is to provide insights for policymakers, industry players, and the public regarding the role of FDI in driving economic growth, technology transfer, and sustainable transportation transitions. The method used is a qualitative descriptive analysis based on official government data, industry reports, company publications, and scientific journals, with a research scope from 2021 to 2025. The results indicate that BYD's investment is driven by Thailand's EV market potential, government incentives, its strategic position in ASEAN, and its mastery of battery and e-axle technologies. The research implications emphasize the importance of targeted policies to attract high-quality FDI.